Thought of Kalam Badî Al-Zamân Said Nursi - Maulana Andi Surya; Mhd. Syahminan; Abrar M Dawud Faza (Budapest International Research and Critics University, 2022)
This article aims to explain more about the background of Said Nursi’s thought, the epistemology of kalam thought, and the results of his kalam thought. This literature study uses a historical (historical), sociological and philosophical approach by extracting data and conducting content analysis. This study shows that: first, the science of kalam must be studied in depth to strengthen beliefs and fortify oneself from the attacks of material thoughts in the modern age, because the highest goal is faith in Allah swt and the noblest degree of humanity is knowledge of Allah swt. Second, Said Nursi’s monotheistic thinking goes beyond the discourse of monotheism and enters the realm of kalam. Therefore, this study uses the term monotheism-kalam. And third, Said Nursi’s tawhid-kalam thinking is closer to Muktazilah theological thinking, because it gives more portion to the use of logic. However, on the other hand, it also looks strong with Asy’ari theological thinking that clings to the text, and is also equipped with the influence of Sufistic thought which he really loves. Another finding is that Said Nursi’s monotheism-kalam thought is considered relevant in the context of diversity in Indonesia because it tends to get out of the kalam debate and eliminate the barriers of fanaticism of certain schools.